2017
DOI: 10.1007/s11356-017-8931-7
|View full text |Cite
|
Sign up to set email alerts
|

Presence of persistent organic pollutants in a breeding common tern (Sterna hirundo) population in Ireland

Abstract: Persistent organic pollutants (POPs) are chemical compounds of environmental concern due to their toxic, persistent nature and their ability to bio-accumulate in biological tissue. Seabirds, for often being at the top of the food web, have been used as monitors of environmental pollutants. Adverse effects caused by POPs have been reported in common terns (Sterna hirundo) since the 1970s. Egg shell thinning, embryo and hatchling deformities have been reported for this species. Environmental legislation, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
0
9
1
Order By: Relevance
“…PCB concentrations were calculated for the EC7 congeners and ranged from 0.19 µg g -1 to 69 µg g -1 . These values were greater than those reported in common terns (Sterna hirundo) from Ireland (0.035 µg g -1 ) (Acampora et al, 2017), and comparable to levels reported in harbour porpoises (Phocoena phocoena) in UK waters (0.4 to 160 µg g -1 ) (Jepson et al, 2016). However, concentrations were approximately one order of magnitude lower than several other marine mammals from European waters where levels of over 100 µg g -1 were regularly detected in bottlenose dolphins (Tursiops truncates), striped dolphins (Stenella coeruleoalba) and killer whales (Orcinus orca) (Jepson et al, 2016).…”
Section: Pcb Concentrations and Signatures In Guillemot Tissuescontrasting
confidence: 73%
“…PCB concentrations were calculated for the EC7 congeners and ranged from 0.19 µg g -1 to 69 µg g -1 . These values were greater than those reported in common terns (Sterna hirundo) from Ireland (0.035 µg g -1 ) (Acampora et al, 2017), and comparable to levels reported in harbour porpoises (Phocoena phocoena) in UK waters (0.4 to 160 µg g -1 ) (Jepson et al, 2016). However, concentrations were approximately one order of magnitude lower than several other marine mammals from European waters where levels of over 100 µg g -1 were regularly detected in bottlenose dolphins (Tursiops truncates), striped dolphins (Stenella coeruleoalba) and killer whales (Orcinus orca) (Jepson et al, 2016).…”
Section: Pcb Concentrations and Signatures In Guillemot Tissuescontrasting
confidence: 73%
“…However, comparisons with internal OCP levels may be affected by (1) differences in blood concentrations at the time of feather formation and at the time of internal tissue sampling, (2) individual or compound-related variations in metabolism, and (3) potential external contamination (see García-Fernández et al 2013). Consequently, there is ambiguous evidence in the literature documenting strong (Eulaers et al 2011;Jaspers et al 2007) and weak significant correlations (Acampora et al 2017;Dauwe et al 2005) between OCP levels in feathers and internal tissues. Nevertheless, feathers are considered suitable for monitoring legacy contaminants such as OCP (Jaspers et al 2019).…”
mentioning
confidence: 99%
“…Birds of all age classes presented the same PCBs accumulation profile, showing the predominance of low-chlorinated PCB congeners, particularly PCB #33, #44 and #31 þ 28, which showed the highest concentrations (juveniles: mean ¼ 30.5, 24.7 and 0.85 ng g À1 ; subadults: mean ¼ 17.4, 14.1 and 10.4 ng g À1 ; adults: mean ¼ 6.91, 6.69 and 16.5 ng g À1 , respectively). High levels of lighter PCBs in birds, including gulls, have been previously reported by several studies, attributing the presence of low chlorinated PCBs congeners in feathers to external contamination (Acampora et al, 2017;Dauwe et al, 2005;Eulaers et al, 2011;Jaspers et al, 2007;Rajaei et al, 2011). It is well known that higher chlorinated compounds are less prominent in aquatic systems due to their lower solubility and volatility.…”
Section: Persistent Organic Pollutants (Pops)mentioning
confidence: 89%
“…This could be attributed to the fact that Olrog's gulls is considered a coastal seabird (in contrast to Procellariiforms ranging in the high seas) whose distribution range along highly impacted coastal areas where pollutants are widely applied (Menone et al, 2006;Pozo et al, 2006). Studies from Norway and Ireland showed a predominance of PCBs over OCPs and PBDEs in feathers of several bird species (Acampora et al, 2017, Briels et al, 2019, Jaspers et al, 2009, Løseth et al, 2019, Svendsen et al, 2018; difference most likely linked to the more intense use of OCPs in South America than in Europe. It is known that Brazil and Argentina are the largest pesticide consumers in South America.…”
Section: Persistent Organic Pollutants (Pops)mentioning
confidence: 99%
See 1 more Smart Citation